VD_FINDINFO HC / 2015 / 1072 vom 27. November 2015 - VD Tribunal cantonal (2015)
PROTECTION DE L'UNION CONJUGALE, OBLIGATION D'ENTRETIEN, MODIFICATION DES CIRCONSTANCES | 176 al. 1 ch. 1 CC, 179 al. 1 CC